Evaluation of the strength and performance of a new hashing algorithm based on a block cipher - Kunbolat Algazy; Kairat Sakan; Nursulu Kapalova (International Journal of Electrical and Computer Engineering (IJECE), 2023)
The article evaluates the reliability of the new HBC-256 hashing algorithm. To study the cryptographic properties, the algorithm was implemented in software using Python and C programming languages. Also, for the algebraic analysis of the HBC-256 algorithm, a system of Boolean equations was built for one round using the Transalg tool. The program code that implements the hashing algorithm was converted into a software program for generating equations. As a result, one round of the compression function was described as conjunctive normal form (CNF) using 82,533 equations and 16,609 variables. To search for a collision, the satisfiability (SAT) problem solver Lingeling was used, including a version with the possibility of parallel computing. It is shown that each new round doubles the number of equations and variables, and the time to find the solution will grow exponentially. Therefore, it is not possible to find solutions for the full HBC256 hash function.